Hubungan antara Narcissistic Trait dan Perilaku Self-Presentation di Instagram pada Dewasa Muda - Emor, Kezia Alexandra; Ninawati, Ninawati (Lembaga Yasin AlSys, 2025)
The use of Instagram as a medium for self-expression has become increasingly dominant among young adults and has sparked academic interest in the personality factors that shape such behavior. This study aimed to examine the relationship between narcissistic traits and self-presentation behavior on Instagram among young adults. A quantitative correlational design was employed with 305 participants aged 18–25 years who were active Instagram users, recruited using convenience sampling. Measurements were conducted using the NPI-16 and POSSA and analyzed with Spearman’s rho. The results showed no significant relationship between narcissistic traits and self-presentation behavior on Instagram (r = 0.004; p = 0.941). These findings indicate that self-presentation behavior on Instagram among young adults is not primarily influenced by narcissistic traits but is likely shaped by other factors beyond the scope of this study, such as social needs, characteristics of the digital environment, or purposes of social media use. This study is expected to serve as a reference for further research on social media user behavior, particularly in identifying other psychological variables and digital contextual factors related to self-presentation patterns.